2013
DOI: 10.1182/blood-2012-09-450031
|View full text |Cite
|
Sign up to set email alerts
|

Hematidrosis: blood sweat

Abstract: A n 18-year-old woman presented with a 6-month mucocutaneous bleeding from the nose, lacrimal ducts, forehead, hands, nails, and navel. Initially bleeding episodes were infrequent, but increased to several times a day by the time of evaluation. Episodes were spontaneous, self-limited, and immediately preceded by intense headache and abdominal pain. Usually high stress was also present. There was no history of previous illnesses. Physical examination showed no signs of self-inflicted lesions. All laboratory, im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 0 publications
2
24
0
Order By: Relevance
“…The bloody sweat excretion can occur in situations of stress or exertion, and can be visualized on physical examination as emanating from the hair follicles [2]. A recent report by Wang et al found only minor extravasation of red blood cells and loosening of the connective tissue on histopathology in a 13-year-old female with hematidrosis [3], and a recent case in an 18-year-old female demonstrated no anatomic anomalies [4]. In these exceedingly rare cases, the laboratory findings are reported as normal and the physical examination may reveal no obvious abnormalities in the absence of discrete bleeding events.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The bloody sweat excretion can occur in situations of stress or exertion, and can be visualized on physical examination as emanating from the hair follicles [2]. A recent report by Wang et al found only minor extravasation of red blood cells and loosening of the connective tissue on histopathology in a 13-year-old female with hematidrosis [3], and a recent case in an 18-year-old female demonstrated no anatomic anomalies [4]. In these exceedingly rare cases, the laboratory findings are reported as normal and the physical examination may reveal no obvious abnormalities in the absence of discrete bleeding events.…”
Section: Discussionmentioning
confidence: 99%
“…The most compelling factor making the diagnosis of hematidrosis less likely in Twinkle is that the initiation of the bleeding episodes was never observed by anyone other than, on several occasions, the patient's mother. Typically, in other reports of this exceptionally rare and poorly defined condition, [3,4] health care providers have directly observed the bleeding whereas in Twinkle's case, the blood was only observed in a drying form following an episode.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hematidrosis is an extremely rare condition. The manifestations of this phenomenon consist of bloody sweat from non‐trauma of the skin and sometimes present with tear blood or bloody otorrhea . The patient has to be ruled out from other bleeding tendency conditions, which can cause spontaneous bleeding episodes.…”
Section: Introductionmentioning
confidence: 99%
“…Hematidrosis, also known as hematohydrosis and hemidrosis, is an episodic, rare skin disease in which blood oozes from the sweat glands . Although its etiopathogenesis is not fully known, it is thought to occur in times of emotional or physical stress . We present an 11‐year‐old patient diagnosed with hematidrosis on the right side of the forehead following trauma, who responded to local adrenaline treatment.…”
mentioning
confidence: 99%